Post-Honeymoon Marriage Dynamics: Couples’ Adaptation in Early Household Life - Nurman Jayadi (IJoIS: Indonesian Journal of Islamic Studies, 2025)
Marriage after the honeymoon phase often shifts from romantic expectations to more complex domestic realities. This study examines how couples adapt to post-honeymoon marital dynamics and maintain household harmony. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving five married couples with 1–5 years of marriage. The findings reveal that communication problems, financial pressures, unequal role distribution, emotional exhaustion, and social media influence are the main challenges experienced by couples in early household life. However, couples who develop open communication, emotional maturity, mutual support, and collaborative problem-solving tend to maintain more stable and harmonious relationships. The study highlights that marital harmony is not solely determined by love and romance, but by the ability to adapt to changing realities and resolve conflicts constructively. The novelty of this research lies in its focus on post-honeymoon adaptation as a continuous relational process shaped by interpersonal communication, emotional resilience, and socio-digital influences in modern married life. This study contributes to family psychology and interpersonal communication studies by emphasizing realistic marital adaptation rather than idealized romantic relationships.